2007
DOI: 10.12968/ijpn.2007.13.8.24536
|View full text |Cite
|
Sign up to set email alerts
|

The development of core competencies for palliative care educators

Abstract: This article outlines the conceptual thinking and development of core competencies for a palliative care educator. It is suggested that the process of defining a common core of key skills, personal qualities and attributes that reflect the unique role of a palliative care educator can provide an indicator of the diversity and complexity of this role, which can be used by the educator and employer in job planning, review and professional development. It can also potentially inform pay remuneration that is comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, participants identified their main focus of attention and association with palliative care on symptom management and the use of technical equipment (syringe driver) in the relief of these symptoms. According to Becker (2007), this narrow view of the role of palliative care (scientific and technical elements) while valued and important, flourishes to the detriment of other intrinsic elements, such as truth telling, spiritual care, ethical issues and understanding grief and loss as a lived experience for patients and families. Moreover, participants failed to recognise the expert role they perform regarding the above elements in symptom management and identified their lack of scientific knowledge regarding symptom management as being a negative factor for them.…”
Section: Aspects Of the Findingsmentioning
confidence: 99%
“…However, participants identified their main focus of attention and association with palliative care on symptom management and the use of technical equipment (syringe driver) in the relief of these symptoms. According to Becker (2007), this narrow view of the role of palliative care (scientific and technical elements) while valued and important, flourishes to the detriment of other intrinsic elements, such as truth telling, spiritual care, ethical issues and understanding grief and loss as a lived experience for patients and families. Moreover, participants failed to recognise the expert role they perform regarding the above elements in symptom management and identified their lack of scientific knowledge regarding symptom management as being a negative factor for them.…”
Section: Aspects Of the Findingsmentioning
confidence: 99%
“…These are the 'core competencies' that healthcare professionals must possess to perform and provide palliative care successfully. [21][22][23][24][25] Palliative care nursing competency is seen as an antecedent to palliative care nursing practice and it is What this paper adds?…”
Section: Introductionmentioning
confidence: 99%
“…However, while the merits of a competency framework are evident, if it is used inappropriately or not understood, it can conversely create a defensive and reductionist approach to practice (Becker, 2007). This study showed that less than half of the participants were using the Framework in practice at the time of evaluation.…”
Section: Discussionmentioning
confidence: 80%